(a2-b2)+(a2-3b2-c)+(5c-2b2-a2) como faço???
Soluções para a tarefa
Respondido por
68
Somar os termos semelhantes:
= (a² - b²) + (a² - 3b² - c) + (5c - 2b² - a²)
= a² - b² + a² - 3b² - c + 5c - 2b² - a²
= a² - b² - 3b² - c + 5c - 2b²
= a² - b² - 3b² - 2b² - c + 5c
= a² - 6b² + 4c
= (a² - b²) + (a² - 3b² - c) + (5c - 2b² - a²)
= a² - b² + a² - 3b² - c + 5c - 2b² - a²
= a² - b² - 3b² - c + 5c - 2b²
= a² - b² - 3b² - 2b² - c + 5c
= a² - 6b² + 4c
Perguntas interessantes
Matemática,
1 ano atrás
Artes,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Música,
1 ano atrás
Matemática,
1 ano atrás